Validación de una técnica electroanalitica para la determinación de paracetamol en medios acuosos enfocados a la ecofarmacovigilancia - Orellana Jaramillo, Ana Marcela (2018)
The contamination of the environment due to the uncontrolled presence of active pharmaceutical ingredients has become a topic of global interest for scientists and the general public, since several studies have identified residues of drugs and their metabolites in rivers , wastewater and even in drinking water. This environmental alteration is due to the inadequate elimination of expired or no longer used drugs and the direct excretion of hospitalized patients to the sewage system, for these reasons is born the Ecofarmacovigilancia that is a science focused on the detection, evaluation and reduction of adverse effects that these can produce the ecosystem. Several organizations that are dedicated to protecting the environment such as the US Environmental Protection Agency (PAE) and the World Health Organization (WHO) have considered that millions of people and animals are exposed to toxic levels of drugs either by the water that is consumed daily, by the soil or by vegetables that may be contaminated. Since studies conducted by researchers at the University of the United States to 139 samples from different streams of different states resulted in alarming amounts of pharmaceutical products (PFs), detecting detergents, pesticides, steroids, NSAIDs, hormones and a variety of antibiotics. The presence of PFs in the water causes adverse effects to marine species such as feminization of male fish, inhibition of growth, mobility and reproducibility of several species of vertebrate and invertebrate animals, even in some cases leading to death. For these reasons we have proposed to validate a low-cost, effective voltammetric technique that helps us detect the presence of Paracetamol (PCT) or Acetaminophen in aqueous media. We report the normalization and validation of an electrochemical method to determine Paracetamol in aqueous media using a μStat - 400 galvanostat potentiostat and a human interaction software / dropview 8400 equipment, both of the Dropsens brand, using a glass - carbon silkscreen electrode ( SGCE) nude containing an integrated auxiliary electrode system (platinum electrode) and reference (Silver Ag / AgCl silver chloride electrode). Several buffer were tested at different pH, the methodology that included 0.1 N sulfuric acid (H2SO4) showed better results, the electrochemical technique chosen was the linear sweep voltammetry (LSV) in a potential range between - 0.1 V and 1.0 V at a scanning speed of 0.05 V / s at a potential step of 0.002 V. Further, With the peak intensity (Ip) of the readings obtained from the scanning of several targets, its standard deviation (DS) of 0.0338 was obtained, achieving a detection limit (LD) of 0.0657 μg / ml or 4.3x10-7 M and a limit of quantification of 0.5759 μg / ml. Several repetitions were made at different concentration levels to determine the precision and accuracy of the method in acceptable ranges obtained in average percentages recovered from the accuracy between 98% to 102%, and for accuracy in our methodology we obtained a DSR of (0,44 % - 1.47 %) being within the acceptable ranges ≤ 2%. Quality control was applied to commercial PCT tablets by using the uv-visible spectrophotometer and Potentiostat, where the accuracy of both methods was compared, obtaining a better recovery percentage with the voltammetric technique; Therefore, we can conclude that our method has the advantage of being more specific in the determination of PCT in the finished product.